Psychometric evaluation of the Arabic version of the Quebec User Evaluation of Satisfaction with Assistive Technology (A-QUEST 2.0) in prosthesis users - (:unkn) unknown (My University, 2021)
BACKGROUND: The evaluation of patient satisfaction and perceptions plays a vital role in determining the quality of prosthesis users' devices and the competency of healthcare services. AIM: To evaluate the psychometric properties of the Arabic Quebec User Evaluation of Satisfaction with Assistive Technology (A-QUEST 2.0) with prosthetics users. DESIGN: A methodological study. SETTING AND POPULATION: A convenience sample of outpatient prosthesis users from Saudi Arabia and Turkey (N=183). METHODS: The A-QUEST 2.0 includes two subscales respectively evaluating the user's satisfaction with the device and the services provided. The data for each subscale were investigated using Rasch analysis to evaluate the item fit, reliability indices, item difficulty, local item dependency, and differential item functioning (DIF). RESULTS: Both subscales met the Rasch criteria for the functioning of rating scale categories. All items showed an acceptable fit to the Rasch model. The person separation indices for the Device and Services subscales were 2.21 (Cronbach's α=0.90) and 1.72 (Cronbach's α=0.85), respectively. Therefore, the two subscales are sensitive enough to distinguish between at least three different levels of satisfaction. The unidimensionality of each subscale was confirmed, and none of the items displayed differential item functioning across age, gender, location of amputation, country, and duration of use. CONCLUSIONS: Overall, the findings indicate the psychometric evaluation of A-QUEST 2.0 is effective with prosthesis users across different clinical contexts and cultures. Thus, the AQUEST 2.0 allows for a comprehensive understanding of users' perceptions of prosthesis characteristics, particularly among subjects with lower limb amputations caused by traumatic injuries. CLINICAL REHABILITATION IMPACT: Our paper provides clinicians dealing with Arabic patients a validated outcome measure for satisfaction with prosthesis. Besides providing information in the development of new products and service delivery. Further studies are necessary to improve the measure's metric quality in different contexts and for different prosthesis devices.